2022
DOI: 10.1155/2022/5748756
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Clinical Significance of lncRNA NEAT1 in Patients with Spinal Tuberculosis

Abstract: Background. Spinal tuberculosis (STB) often leads to irreversible neurological injury, resulting in serious social and economic problems. With the emergence of drug resistance, the management becomes even more challenging, given the treatment courses are generally longer for skeletal than pulmonary tuberculosis (PTB). The development and validation of nonsputum biomarkers for diagnosis and tailoring of treatment duration to enable personalized and evidence-based management of such diseases to improve treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…lncRNA SNHG15 expression was significantly increased in tuberculosis lesion tissues, and inhibiting it could down‐regulate the formation and proliferation of osteoclasts, which are obviously associated with tuberculosis, thereby promoting disease recovery 15 . Zheng et al 135 revealed that lncRNA NEAT1 levels were correlated with paravertebral abscess, multi‐segment involvement, and the anti‐tuberculosis treatment outcome, with increased expression mostly indicating a good prognosis. Matrix metalloproteinases (MMPs) are engaged in extracellular matrix decomposition in normal physiological and disease processes.…”
Section: Future Prospectmentioning
confidence: 99%
“…lncRNA SNHG15 expression was significantly increased in tuberculosis lesion tissues, and inhibiting it could down‐regulate the formation and proliferation of osteoclasts, which are obviously associated with tuberculosis, thereby promoting disease recovery 15 . Zheng et al 135 revealed that lncRNA NEAT1 levels were correlated with paravertebral abscess, multi‐segment involvement, and the anti‐tuberculosis treatment outcome, with increased expression mostly indicating a good prognosis. Matrix metalloproteinases (MMPs) are engaged in extracellular matrix decomposition in normal physiological and disease processes.…”
Section: Future Prospectmentioning
confidence: 99%